Activation of P2X4 receptors induces an increase in the area of the extracellular region and a decrease in receptor mobility. Issue 24 (10th October 2020) - Bergler, Frederik; Fuentes, Christian; Kadir, Md. Fahim; Navarrete, Camilo; Supple, Jack; Barrera, Nelson P.; Edwardson, John Michael
Abstract : The P2X4 receptor (P2X4R) is an ATP‐gated cation channel. Here, we used fast‐scan atomic force microscopy (AFM) to visualize changes in the structure and mobility of individual P2X4Rs in response to activation. P2X4Rs were purified from detergent extracts of transfected cells and integrated into lipid bilayers. Activation resulted in a rapid (2 s) and substantial (10–20 nm 2 ) increase in the cross‐sectional area of the extracellular region of the receptor and a corresponding decrease in receptor mobility. Both effects were blocked by the P2X4R antagonist 5‐BDBD. Addition of cholesterol to the bilayer reduced receptor mobility, although the ATP‐induced reduction in mobility was still observed. We suggest that the observed responses to activation may have functional consequences for purinergic signalling.